The glass menagerie: a play - Keathley, George; Pitkin, William; Williams, Tennessee, 1911-1983.; Coe, Richard L. (Richard Livingstone), 1914-1995; Theatre Guild. American Repertory Company; National Theatre Corporation (Washington, D.C.); Richard L. Coe Theater Programs Collection (Library of Congress) (New York : The New Classics, 1960)
National Theatre, Louis A. Lotito, managing director, The Theatre Guild American Repertory Company, produced by the Theatre Guild Foundation for the president's special international program under the auspices of the United States Department of State, Helen Hayes, Leif Erickson, June Havoc, Helen Menken in "The Skin of Our Teeth," by Thornton Wilder, "The Glass Menagerie," by Tennessee Williams, "The Miracle Worker," by William Gibson, with Nancy Coleman, James Broderick, Barbara Barrie, Dorothy Sands, Romney Brent, Rona Gale, each play produced under the personal supervision of the author. "The Glass Menagerie," by Tennessee Williams, staged by George Keithley, designed by William Pitkin, original music composed by Paul Bowles, produced under the personal supervision of Mr. Williams.
Title devised by Library staff.
"The first dramatic company especially created for the U.S. State Department and the American National Theatre and Academy to tour the major capitals of Western Europe, the Near East and Latin America".
Cast: Helen Hayes, James Broderick, Nancy Coleman, Leif Erickson.
LC copy has notations by Coe. Shelved under: Skin of our teeth.
With: The skin of our teeth / Thornton Wilder. Issued together.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1960.